Integrating evidence into policy and sustainable disability services delivery in western New South Wales, Australia: the 'wobbly hub and double spokes' project - Veitch Craig; Lincoln Michelle; Bundy Anita; Gallego Gisselle; Dew Angela; Bulkeley Kim; Brentnall Jennie; Griffiths Scott (BMC, 2012)
Abstract Background Policy that supports rural allied health service delivery is important given the shortage of services outside of Australian metropolitan centres. The shortage of allied health professionals means that rural clinicians work long hours and have little peer or service support. Service delivery to rural and remote communities is further complicated because relatively small numbers of clients are dispersed over large geographic areas. The aim of this five-year multi-stage project is to generate evidence to confirm and develop evidence-based policies and to evaluate their implementation in procedures that allow a regional allied health workforce to more expeditiously respond to disability service need in regional New South Wales, Australia. Methods/Design The project consists of four inter-related stages that together constitute a full policy cycle. It uses mixed quantitative and qualitative methods, guided by key policy concerns such as: access, complexity, cost, distribution of benefits, timeliness, effectiveness, equity, policy consistency, and community and political acceptability. Stage 1 adopts a policy analysis approach in which existing relevant policies and related documentation will be collected and reviewed. Policy-makers and senior managers within the region and in central offices will be interviewed about issues that influence policy development and implementation. Stage 2 uses a mixed methods approach to collecting information from allied health professionals, clients, and carers. Focus groups and interviews will explore issues related to providing and receiving allied health services. Discrete Choice Experiments will elicit staff and client/carer preferences. Stage 3 synthesises Stage 1 and 2 findings with reference to the key policy issues to develop and implement policies and procedures to establish several innovative regional workforce and service provision projects. Stage 4 uses mixed methods to monitor and evaluate the implementation and impact of new or adapted policies that arise from the preceding stages. Discussion The project will provide policy makers with research evidence to support consideration of the complex balance between: (i) the equitable allocation of scarce resources; (ii) the intent of current eligibility and prioritisation policies; (iii) workforce constraints (and strengths); and (iv) the most effective, evidence-based clinical practice.